Ethnic Swedish Parents' experiences of minority ethnic nurses' cultural competence in Swedish paediatric care. Issue 2 (5th May 2013) - Tavallali, Azar G.; Kabir, Zarina Nahar; Jirwe, Maria
<x xml:space="preserve">Abstract</x> Background Sweden has a population of a little more than 9.4 million. The rapid growth of immigration in Sweden has resulted in an increased number of minority ethnic patients and minority ethnic nurses in the Swedish healthcare system. This also applies to paediatric care. Aim The purpose of this study was to explore how parents with ethnic Swedish backgrounds experience minority ethnic nurses' cultural competence and the care the nurses provide in a Swedish paediatric care context. Method This exploratory qualitative study is of 14 parents with an ethnic Swedish background whose child was in a ward at a children's hospital in Stockholm County Council. Data were collected using semi‐structured interviews to identify parents' perceptions and experiences of minority ethnic nurses' cultural competence. The interviews were analysed by qualitative content analysis. Results The analyses of the interviews led to four main categories: influence of nurses' ethnicity; significance of cross‐cultural communication; cross‐cultural skills; and the importance of nursing education. Conclusions Nurses' ethnicity did not have much impact on parents' satisfaction with their child's care. The parents attached importance to nurses' language skills and to their adaptation and awareness of Swedish culture. They also attached weight to nurses' professional knowledge and personal attributes. The role of nursing education to increase nurses' cultural awareness was highlighted too.